2019
DOI: 10.1071/ch19336
|View full text |Cite
|
Sign up to set email alerts
|

Oil Spill Source Identification Using Colorimetric Detection

Abstract: The colorimetric detection of polycyclic aromatic hydrocarbons (PAHs) was investigated for the quick and easy identification of likely oil spill offenders. In this new technology, photochromic compounds were used to sense PAHs by varying their photoswitching capacity. To that end, three photochromes were designed and showed varying degrees of photoswitching inhibition, depending on PAH analyte, photochrome, and excitation wavelength. PAH mixtures that mimic oil spills showed the same varying response and demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…indicating an extension of the conjugation in both the open (336 vs 365 nm) and closed (618 vs 625 nm) isomeric forms of the polymers (Figure S2, Supporting Information). [47] P5 displayed a maximum absorption at 365 nm, which is similar to P1-P3, and is expected since polyfluorenes and polycarbazoles have a similar absorption maximum. [48] The emergence of a higher energy peak at 272 nm is also typical to carbazole based polymers and related to 𝜋-𝜋* electronic transition of the conjugation.…”
Section: Solution Physicochemical Propertiessupporting
confidence: 65%
See 1 more Smart Citation
“…indicating an extension of the conjugation in both the open (336 vs 365 nm) and closed (618 vs 625 nm) isomeric forms of the polymers (Figure S2, Supporting Information). [47] P5 displayed a maximum absorption at 365 nm, which is similar to P1-P3, and is expected since polyfluorenes and polycarbazoles have a similar absorption maximum. [48] The emergence of a higher energy peak at 272 nm is also typical to carbazole based polymers and related to 𝜋-𝜋* electronic transition of the conjugation.…”
Section: Solution Physicochemical Propertiessupporting
confidence: 65%
“…Polymers based on fluorene, phenylene and carbazole comonomer showed cyclization quantum yields over 0.5 suggesting a primarily antiparallel conformation of the dithienylethene moieties. [30,47] The photoswitching properties were not molecular weight dependent, where lower molecular weight analogues of P1, P3, and P4 (Table S1, Supporting Information) had similar quantum yields of cycliza-tion. Cycloreversion quantum yields varied between 0.004 and 0.011 and are typical for DTE based materials.…”
Section: Solution Physicochemical Propertiesmentioning
confidence: 99%
“…It is concluded that this may be a viable technique for in situ oil identification. [6] Craig Williams and colleagues at the University of Queensland report an investigation into 1,2,4-thiadiazole-inspired cyclic peptide mimics. Marine-derived cyclic peptides have cavitand architectures comparable with macrocyclic ligands.…”
mentioning
confidence: 99%